2022
DOI: 10.1002/ejsp.2818
|View full text |Cite
|
Sign up to set email alerts
|

Does crossing a moral line justify collective means? Explaining how a perceived moral violation triggers normative and nonnormative forms of collective action

Abstract: contributed equally and order was determined alphabetically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
(80 reference statements)
1
21
0
Order By: Relevance
“…In line with the documented importance of moral emotions, attitude moralization is likely tied to the motivation to protect the integrity of one’s core moral values against perceived moral transgressions by others (i.e., psychological value protection ; for example, Tetlock et al, 2000 ). For example, recent experimental findings showed that perceived value violations (e.g., blatant discrimination of Muslims or women by the U.S. president) predicted increased attitude moralization about a specific government policy (e.g., the U.S. travel ban; Pauls et al, in press ). Comparably, other research found that perceived value violations in the context of gender equality increased attitude moralization specifically when the perpetrating outgroup was perceived as immoral (rather than neutral or moral; Leal, van Zomeren, Gordijn, et al, 2020 ).…”
Section: An Integrative Model Of Attitude Moralization In Polarized C...mentioning
confidence: 99%
“…In line with the documented importance of moral emotions, attitude moralization is likely tied to the motivation to protect the integrity of one’s core moral values against perceived moral transgressions by others (i.e., psychological value protection ; for example, Tetlock et al, 2000 ). For example, recent experimental findings showed that perceived value violations (e.g., blatant discrimination of Muslims or women by the U.S. president) predicted increased attitude moralization about a specific government policy (e.g., the U.S. travel ban; Pauls et al, in press ). Comparably, other research found that perceived value violations in the context of gender equality increased attitude moralization specifically when the perpetrating outgroup was perceived as immoral (rather than neutral or moral; Leal, van Zomeren, Gordijn, et al, 2020 ).…”
Section: An Integrative Model Of Attitude Moralization In Polarized C...mentioning
confidence: 99%
“…There is ample research on factors associated with normative collective action. Considering that empirical findings regarding morality perceptions and non‐normative collective action are mixed, with some studies showing effects of morality perceptions only on normative collective action (e.g., Cocco et al, 2022) and others on both collective action forms (e.g., Pauls et al, 2022), we do not make a‐priori predictions.…”
Section: The Present Researchmentioning
confidence: 87%
“…When this happens, individuals are likely to be motivated to protect identity relevant values under threat (Van Zomeren et al, 2018; see also Radke et al, 2020). Research has consistently shown that moral violation can lead to increased collective action, also in its more radical, non-normative forms (Pauls, Shuman, Van Zomeren, Saguy, & Halperin, 2022).…”
Section: Morality Perceptions As Mediatorsmentioning
confidence: 99%
“…Moral convictions can therefore serve as predictors of collective action on the basis of identification with a specific social identity that incorporates these principles. Research has consistently shown that moral convictions are associated with greater intentions to engage in collective action (Pauls et al, 2021;Skitka & Bauman, 2008;Skitka et al, 2005;van Zomeren et al, 2011van Zomeren et al, , 2012van Zomeren et al, , 2018Zaal et al, 2011).…”
Section: The Power Of Moral Convictionsmentioning
confidence: 99%